2014
DOI: 10.3109/09637486.2014.908172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water soaking and/or sodium polystyrene sulfonate addition on potassium content of foods

Abstract: In this study, we determined, by atomic absorption spectrophotometry, the potassium amount leached by soaking or boiling foods identified by children suffering from chronic renal failure as "pleasure food" and that they cannot eat because of their low-potassium diet, and evaluated whether addition of sodium polystyrene sulfonate resin (i.e. Kayexalate®) during soaking or boiling modulated potassium loss. A significant amount of potassium content was removed by soaking (16% for chocolate and potato, 26% for app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Similar results were found also by Aiimwe et al who showed that soaking did not change potassium content in a particular type of banana while boiling at 200 °C reduced potassium concentration from 1.4 ppm to 1 ppm after 60 min [ 37 ]. Poor results with soaking were found also by Picq et al with various types of foods ( Table 4 ) [ 40 ]. Preparation of food seems to be important: boiling potatoes after cubing or shredding results in a much greater loss of potassium [ 41 ].…”
Section: Dietary Intervention To Limit Potassium Intakementioning
confidence: 67%
See 1 more Smart Citation
“…Similar results were found also by Aiimwe et al who showed that soaking did not change potassium content in a particular type of banana while boiling at 200 °C reduced potassium concentration from 1.4 ppm to 1 ppm after 60 min [ 37 ]. Poor results with soaking were found also by Picq et al with various types of foods ( Table 4 ) [ 40 ]. Preparation of food seems to be important: boiling potatoes after cubing or shredding results in a much greater loss of potassium [ 41 ].…”
Section: Dietary Intervention To Limit Potassium Intakementioning
confidence: 67%
“…Additional aspects useful to limit effective potassium intake is education about the use of cooking procedures (as soaking or boiling) in order to obtain food demineralization [ 37 , 38 , 39 , 40 , 41 ]: boiling is able to remove up to 60–80% of the potassium content of several raw foods ( Table 4 )…”
Section: Dietary Intervention To Limit Potassium Intakementioning
confidence: 99%
“…There appears to be a linear dose relationship, with higher doses of SPS predictably being associated with greater reductions in potassium. Pretreating EN with doses of SPS >1 g/mEq K does not appear to confer any additional reduction in potassium content but may result in greater increases in sodium content in EN, ultimately increasing the risk of hypernatremia [ 7 , 8 ]. Half of the patients in our cohort who received SPS doses ≤0.6 g/mEq K developed adverse effects as compared with 60% of patients who received higher SPS doses.…”
Section: Discussionmentioning
confidence: 99%
“…Tomato fruits are rich in K + . While K + intake is useful for preventing hypertension [49], it is necessary to suppress intake in renal dysfunction [50]. Therefore, control of the K + concentration related to SlCCX is an important issue.…”
Section: Expression Profile Of Slcaca Genes In Vegetative Organs Flomentioning
confidence: 99%